Hydrogen Ion Entry as a Controlling Factor in the Acid-growth Response of Green Pea Stem Sections - Cleland, Robert E. (1975)
The ability of green pea (Pisum sativum var. Alaska) stem sections to elongate in response to H(+) has been reinvestigated. Contrary to the conclusions of Barkley and Leopold, (Plant Physiol. 1973. 52: 76-78) these sections elongate in response to H(+) whenever H(+) entry through the cuticle is facilitated by slits, holes, or removal. Both live and frozen-thawed sections can undergo acid-induced elongation. Green pea stems behave as predicted by the acid-growth theory.